Evaluation of a protocol exercises for musicians with musculoskeletal problems - Rodrigues, Abel (2014)
Introduction: Work-Related Musculoskeletal Disorders (MSDs), associated with execution of musical performance, are usually referred to the upper limb, neck and lumbar spine. Objective: The general objective of this study is to evaluate the effectiveness of an exercises protocol of muscle relaxation in the decrease of pain, discomfort and activity levels of the neck and shoulder muscles in different types of musicians with musculoskeletal disorders. Methods: The sample was composed by 12 students of the music course of Escola Superior de Artes Aplicadas de Castelo Branco, who were divided in two groups: strings (7 participants) and wind (5 participants). The sample was composed by 7 male and 5 female musicians with an average age of 20,75 years. Data collection was performed in two stages: T0 before the realization of protocol and T1 after the application of the intervention. In the two moments, the instruments and scales used were the Surface Electromyography (sEMG), Visual Analogue Scale (VAS) of pain and discomfort in the neck-shoulder and Neck and Upper Limb Index (NULI-20). About EMG, the data collection was realized while participants performed a 15 minutes repertoire wherein the muscles evaluated were the trapezius (upper, middle and lower) and the deltoids (anterior, middle and posterior). Intervention protocol consisted in relaxation and stretching exercises of the muscles in study realized in class and autonomous execution in the beginning, break and final of the instrumental daily practice of each one of the participants with duration of 4 weeks. Results: There is a significative decrease in the VAS of pain (p=0,008) and discomfort (p=0,012) but not significative in the values of NULI-20 and RMS (p>0,05). Conclusions: Intervention protocol applied in this study was effective in the decreased intensity of pain and discomfort and contributed to the decrease of the values of NULI-20 and myoelectric activity levels of trapezius and deltoids, although without significance. These results confirm the idea that prevention programs should be early implemented in music schools in order to avoid the appearance of PRMD in this population.